2018
DOI: 10.1002/2017wr021806
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Hydrology of the Glacierized Kaidu Basin by Integrating Multisource Data in the Tianshan Mountains, Northwestern China

Abstract: Understanding the water balance, especially as it relates to the distribution of runoff components, is crucial for water resource management and coping with the impacts of climate change. However, hydrological processes are poorly known in mountainous regions due to data scarcity and the complex dynamics of snow and glaciers. This study aims to provide a quantitative comparison of gridded precipitation products in the Tianshan Mountains, located in Central Asia and in order to further understand the mountain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Previous studies indicated that the TS have experienced a significant warming trend over the past few decades [44][45][46]. The snowfall/precipitation ratio showed a decreasing trend accompanied by increasing temperatures in the TS [47], which intensified glacier and snow melt [2], leading to increasing runoff and earlier peak runoff from glacier/snow melt in these recharging river basins [45,[48][49][50]. Several studies have investigated the impact of glacier change on water resources in the TS [42,51-53], but only a few studies have addressed the snow cover changes with optical remote sensing [54,55].…”
mentioning
confidence: 99%
“…Previous studies indicated that the TS have experienced a significant warming trend over the past few decades [44][45][46]. The snowfall/precipitation ratio showed a decreasing trend accompanied by increasing temperatures in the TS [47], which intensified glacier and snow melt [2], leading to increasing runoff and earlier peak runoff from glacier/snow melt in these recharging river basins [45,[48][49][50]. Several studies have investigated the impact of glacier change on water resources in the TS [42,51-53], but only a few studies have addressed the snow cover changes with optical remote sensing [54,55].…”
mentioning
confidence: 99%
“…These findings are in agreement with the results of a study by Shen et al in the Kaidu Basin in Central Asia. Shen et al [37] used gridded products, including CFSR, APHRODITE, CRU, TRMM, ERA-Interim and MERRA-2, with the J2000 model to analyze the spatiotemporal patterns of water balance and the distribution of runoff components in the glacierized Kaidu Basin in Central Asia. The results showed that APHRODITE and CRU represented annual and seasonal precipitation dynamics that were similar to the observational dataset at most climate points [37].…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al [37] used gridded products, including CFSR, APHRODITE, CRU, TRMM, ERA-Interim and MERRA-2, with the J2000 model to analyze the spatiotemporal patterns of water balance and the distribution of runoff components in the glacierized Kaidu Basin in Central Asia. The results showed that APHRODITE and CRU represented annual and seasonal precipitation dynamics that were similar to the observational dataset at most climate points [37]. Similarly, a water balance study with the application of the SWAT model and observational datasets was conducted in the Indian Ken River Basin in South Asia, from 1986 to 2005 [20].…”
Section: Discussionmentioning
confidence: 99%
“…The glacial meltwater in the upper Kaidu River basin directly affects the availability of water downstream seasonally for its potential uses, such as for human consumption, irrigation, industry, etc. Losses in glacier volume also influence the seasonal timing and variability of streamflow (Shen and others, 2018). These hydrological changes will influence future water management decisions in the region regarding intra- and inter-basin water transfers, irrigation and dam construction (Chipman and others, 2016).…”
Section: Discussionmentioning
confidence: 99%